(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The age and stratigraphic subdivisions for the late Oligocene-Miocene, marine deposits of Patagonia (Patagoniense succession) have been largely debated. Most studies for the Comodoro Rivadavia region were focused on its biostratigraphy and stratigraphic relations with the underlying and overlying mammal-bearing terrestrial strata. We report here thirteen new 86Sr/87Sr ages obtained from wellpreserved oyster valves of the Chenque Formation in the classical Patagoniense outcrops around the city of Comodoro Rivadavia (Golfo San Jorge Basin, Argentina). According to these ages, the deposition of the unit in the region occurred between 19.69 and 15.37 Ma (Burdigalian-early Langhian). A lower interval of normal sedimentation rate (Sequences 1 and 2) and an upper interval of high sedimentation rate (Sequence 3) are defined according to these new ages of the Chenque Formation. Subsequently, the depositional age of the Chenque Formation is compared with other well-dated marine successions of southern Patagonia located within the Austral Basin. This analysis suggests that the Austral and Golfo San Jorge basins were flooded by the Atlantic sea at about the same time ( 21-20 Ma), inundating what was before a vast continental region of southern Patagonia. A renewed phase of continentalization occurred at about 18 Ma in the Austral Basin and at about 15 Ma in the study region of the Golfo San Jorge Basin. This 3 my difference combined with the elevated sedimentation rate estimated for the upper part of the study interval, suggest that the Golfo San Jorge Basin may have locally experienced relatively high subsidence rates during the early Miocene, allowing prolonged marine sedimentation in the Comodoro Rivadavia area. Consequently, the accumulation of the terrestrial deposits assigned to the Santa Cruz Formation started at about 15 Ma in the study region, later than in other localities of southern Patagonia. This results clearly indicate a remarkable interdigitation between the Santa Cruz and Chenque formations in a west-east transect across central Patagonia.